Dietary supplementation with d-tagatose in subjects with type 2 diabetes leads to weight loss and raises high-density lipoprotein cholesterol - Donner, Thomas W.; Magder, Laurence S.; Zarbalian, Kiarash (Nutrition research (New York, N.Y.), 2010)
Oral d-tagatose ( d-tag) attenuates the rise in plasma glucose during an oral glucose tolerance test in subjects with type 2 diabetes mellitus (DM) and reduces food intake in healthy human subjects. A reduction in food consumption and less weight gain occur in rats fed tagatose. This pilot study explored the metabolic effects of d-tag given daily to 8 human subjects with type 2 DM for 1 year. We hypothesized that this treatment period would lead to weight loss and improvements in glycated hemoglobin and the lipid profile. A 2-month run-in period was followed by a 12-month treatment period when 15 g of oral d-tag was taken 3 times daily with food. No serious adverse effects were seen during the 12-month treatment period. Ten of the initially12 recruited subjects experienced gastrointestinal side effects that tended to be mild and transient. When 3 subjects were excluded who had oral diabetes, medications added and/or dosages increased during the study and mean (SD) body weight declined from 108.4 (9.0) to 103.3 (7.3) kg ( P = .001). Glycated hemoglobin fell nonsignificantly from 10.6% ± 1.9% to 9.6% ± 2.3% ( P = .08). High-density lipoprotein cholesterol progressively rose from a baseline level of 30.5 ± 15.8 to 41.7 ± 12.1 mg/dL at month 12 in the 6 subjects who did not have lipid-modifying medications added during the study ( P < .001). Significant improvements in body weight and high-density lipoprotein cholesterol in this pilot study suggest that d-tag may be a potentially useful adjunct in the management of patients with type 2 DM.